2013
DOI: 10.1007/s00277-013-1829-7
|View full text |Cite
|
Sign up to set email alerts
|

The characteristics of ascites in patients with POEMS syndrome

Abstract: The characteristics of ascites in patients with POEMS syndrome, which comprise polyneuropathy, organomegaly, endocrinopathy, M protein, and skin changes, are unknown. We described the frequency of ascites at presentation of POEMS syndrome and further evaluated for the pathogenesis and nature of the ascites. One hundred and six consecutive patients with POEMS syndrome in Chinese PLA General Hospital were evaluated for the presence of ascites, and the cellular and biochemical characteristics of the ascitic fluid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 20 publications
2
19
1
1
Order By: Relevance
“…(3,5,19), but was 87.5% when assessed by CT in the current study. By ultrasonography ascites were reported in 39.6% patients from a Chinese report (5) and were detected in 44.4% patients in this study, but ascites were detected by CT in 54.2% patients in the current study. The differences between detection rates by ultrasonography and by CT are probably due to the small volume of effusion which can only be detected by more sensitive CT.…”
Section: Discussioncontrasting
confidence: 79%
“…(3,5,19), but was 87.5% when assessed by CT in the current study. By ultrasonography ascites were reported in 39.6% patients from a Chinese report (5) and were detected in 44.4% patients in this study, but ascites were detected by CT in 54.2% patients in the current study. The differences between detection rates by ultrasonography and by CT are probably due to the small volume of effusion which can only be detected by more sensitive CT.…”
Section: Discussioncontrasting
confidence: 79%
“…The composition of the ascites was studied in 42 patients with POEMS syndrome. The ascitic fluid had low serum ascites albumin gradients consistent with an exudative rather than a portal hypertension process in 74% of cases [65].…”
Section: Diagnosismentioning
confidence: 97%
“…However according to a recent study of 42 patients with ascites, they all demonstrated a SAAG of <1.1, suggesting a nonportal hypertensive cause. 3 This was not the case for this particular patient. She had 2 paracenteses that showed a SAAG of >1.1 before diagnosis.…”
Section: Conflicts Of Interestmentioning
confidence: 72%